Changes in Pedagogical Interaction in the Context of Productive Learning - Petruškevičiūtė, Auksė (Pedagogika, 2015)
Productive Learning, an educational innovation in the education system of Lithuania, whose theoretical paradigms and methodology enable widening the scope of the concept of pedagogical interaction to the conceptual scope of educational interaction, is presented in this article. Social actors surrounding the young person, i.e. peer students, local community, various entities of the labour market, are being consistently involved into the process of his / her self-education. A student in cooperation with a teacher and other actors of the self-educational process design the self-education content that meets his / her individual needs, while the process of self-education of a student is integrated into the process of learning at sites of practical training that are selected by himself / herself. Productive Learning is introduced as a “branch” of Alternative Education in Lithuania’s education system. Its target-group is students of Forms 9–10 who experience lasting failures at school and are attributed to the risk group of early school leavers. In this article, changes at student, teacher and school level caused by the educational interaction taking place in the context of Productive Learning are discussed and the main impediments for building the educational interaction in the new environment are disclosed. Building on the results of the empirical study that are corresponding those obtained in other countries (Germany, Finland) where Productive Learning is being adopted, an assertion can be made that the educational interaction being developed in Productive Learning leads to positive changes. Therefore, Productive Learning can be transferred and adopted in the education system of Lithuania as a feasible and effective pedagogical system. The results and conclusions of the study bear relevance for education policymakers, researchers and practicians who are looking for new and effective possibilities for development of (self-) educational processes and those who conduct a deeper analysis of the phenomenon of educational interaction.